2012
DOI: 10.1063/1.3692973
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of the system of two falling balls

Abstract: We consider the motion of two point masses along a vertical half-line that are subject to constant gravitational force and collide elastically with each other and the floor. This model was introduced by Wojtkowski who established hyperbolicity and ergodicity in case the lower ball is heavier. Here, we investigate the dynamics in discrete time and prove that, for an open set of the external parameter (the relative mass of the lower ball), the system mixes polynomially-modulo logarithmic factors, correlations de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(31 citation statements)
references
References 38 publications
(72 reference statements)
2
29
0
Order By: Relevance
“…By detailed analysis of the geometry of the system we identify special periodic points and show that the ratio of certain periods in continuous time is Diophantine for almost every value of the mass parameter in an interval. Using results of Melbourne ([13]) and our previous achievements [1] we conclude that for these values of the parameter the flow mixes faster than any polynomial. Even though the calculations are presented for the specific physical system, the method is quite general and can be applied to other suspension flows, too.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…By detailed analysis of the geometry of the system we identify special periodic points and show that the ratio of certain periods in continuous time is Diophantine for almost every value of the mass parameter in an interval. Using results of Melbourne ([13]) and our previous achievements [1] we conclude that for these values of the parameter the flow mixes faster than any polynomial. Even though the calculations are presented for the specific physical system, the method is quite general and can be applied to other suspension flows, too.…”
mentioning
confidence: 64%
“…It can be shown that τ is piecewise C 2 with the same discontinuities as the discrete time dynamics T (see [1], subsection 3.7 for details). The flow is then isomorphic to the following suspension.…”
Section: Statement Of Resultsmentioning
confidence: 99%
See 3 more Smart Citations